2017
DOI: 10.1128/aac.02360-16
|View full text |Cite
|
Sign up to set email alerts
|

Meglumine Antimoniate (Glucantime) Causes Oxidative Stress-Derived DNA Damage in BALB/c Mice Infected by Leishmania (Leishmania) infantum

Abstract: Leishmaniasis is a neglected tropical disease caused by Ͼ20 species of the protozoan parasite Leishmania. Meglumine antimoniate (Glucantime) is the firstchoice drug recommended by the World Health Organization for the treatment of all types of leishmaniasis. However, the mechanisms of action and toxicity of pentavalent antimonials, including genotoxic effects, remain unclear. Therefore, the mechanism by which meglumine antimoniate causes DNA damage was investigated for BALB/c mice infected by Leishmania (Leish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 53 publications
(58 reference statements)
2
32
0
Order By: Relevance
“…Considering that our research group has demonstrated that meglumine antimoniate causes oxidation of nitrogenous bases on DNA and alters oxidant enzymes activities in BALB/c mice infected by Leishmania (Leishmania) infantum, leading to genomic instability and mutation fixation (23), and keeping in mind that antioxidant compounds neutralize deleterious actions of ROS on biomolecules (24,25), the aim of this study was to evaluate the potential of two acknowledged antioxidants (genistein and ascorbic acid) in modulating genetic damage caused by the antileishmanial meglumine antimoniate.…”
mentioning
confidence: 99%
“…Considering that our research group has demonstrated that meglumine antimoniate causes oxidation of nitrogenous bases on DNA and alters oxidant enzymes activities in BALB/c mice infected by Leishmania (Leishmania) infantum, leading to genomic instability and mutation fixation (23), and keeping in mind that antioxidant compounds neutralize deleterious actions of ROS on biomolecules (24,25), the aim of this study was to evaluate the potential of two acknowledged antioxidants (genistein and ascorbic acid) in modulating genetic damage caused by the antileishmanial meglumine antimoniate.…”
mentioning
confidence: 99%
“…(Glucantime) is a pentavalent antimony (Sb V ) recommended by the World Health Organization as the first-choice drug for the treatment of all types of leishmaniasis; the maximum dose recommended is 20 mg/kg of body weight/day via the intramuscular route. Although pentavalent antimonials have been used for many years, the pharmacological and toxicological mechanisms involved in their action remain unclear [5]. Berman et al [6] and Demicheli et al [7] proposed that this drug interferes with the bioenergetic process of Leishmania amastigotes, which inhibit parasites fatty acid -oxidation and glycolysis, promoting the depletion of intracellular ATP levels.…”
Section: Introductionmentioning
confidence: 99%
“…The most frequently reported clinical adverse effects are musculoskeletal pain, nausea, vomiting, diarrhea, abdominal pain, headache, anorexia, asthenia, fatigue, fever, exanthema, erythema, and urticaria. Moreover, patients may develop cardiac, liver, and kidney complications, usually at the end of the treatment [9].…”
Section: Introductionmentioning
confidence: 99%
“…On 29.01.18 (on the 19th day of the treatment), the general condition of the patient continued to worsen, as the signs of general intoxication have intensified, manifesting themselves through pronounced physical asthenia, muscle pain, arthralgia, fever over 39.0 ° C, and insomnia. These symptoms were considered to be caused by the adverse reaction to treatment with Meglumine antimonate [18,25]. Following the occurrence of these side effects, the dose of antimony meglumine was reduced to 5 ml/day.…”
Section: Resultsmentioning
confidence: 99%
“…Patients who have previously had cutaneous leishmaniasis acquired in certain parts of the New World are at risk for mucocutaneous leishmaniasis [14]. Meglumine antimoniate (Glucantime) is a pentavalent antimony (Sb V ) recommended by the World Health Organization as the first-choice drug for the treatment of all types of leishmaniasis; the maximum dose recommended is 20 mg/kg of body weight/day via the intramuscular route [4,5,15,25]. Some of the side-effects may be rare but serious: fever, irregular heartbeat, nausea, back pain, upper abdominal pain, vomiting, chills, cough, skin rash, drowsiness [18,].…”
Section: Introductionmentioning
confidence: 99%